Timur Kuran: The Long Divergence: How Islamic Law Held Back the Middle East. Princeton (New Yersey), Princeton University Press, 2011, 405 págs. - Barquín Gil, Rafael (Investigaciones de Historia Económica, 2019)
Sin resumen